2019
DOI: 10.24099/vet.arhiv.0340
|View full text |Cite
|
Sign up to set email alerts
|

CYP11B1 and PPARGC1A genes polymorphism controlling reproductive traits and estimation of breeding value of first lactation milk yield in Bos indicus (Deoni) cattle

Abstract: BaSak, S., D. N. DaS, U. T. MUNDhe: CYP11B1 and PPARGC1A genes polymorphism controlling reproductive traits and estimation of breeding value of first lactation milk yield in Bos indicus (Deoni) cattle. Vet. arhiv 89, 463-479, 2019. aBSTRaCT In the present study, in Deoni, the dual purpose cattle breed of Southern India, maintained in a National Dairy Research Institute herd, Southern Regional Station, Bengaluru, molecular characterization of the putative exon 1 of CYP11B1 and putative intron 9 and 3'UTR of PPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The non-significant chisquare value indicated that all the genotypic frequencies in the population were not in Hardy-Weinberg equilibrium (P>0.01). The current study's findings are in line with the results reported byBasak et al (2019) in 146 Deoni breeds of cattle for AA, AC and CC genotypes with frequencies as 0.75, 0.21 and 0.04, respectively. For this locus, Kowalewska-Łuczak et al (2010) also found two genotypes i.e.…”
supporting
confidence: 92%
“…The non-significant chisquare value indicated that all the genotypic frequencies in the population were not in Hardy-Weinberg equilibrium (P>0.01). The current study's findings are in line with the results reported byBasak et al (2019) in 146 Deoni breeds of cattle for AA, AC and CC genotypes with frequencies as 0.75, 0.21 and 0.04, respectively. For this locus, Kowalewska-Łuczak et al (2010) also found two genotypes i.e.…”
supporting
confidence: 92%